The gas flow through the laser-sustained plasmas - Szymański, Z. (Archives of Mechanics, 1998)
Modelling of the laser-sustained plasmas (LSP) in a forced convective flow is presented. The emphasis is put on the modelling of the flow through the region of elevated temperature. Theoretical quasi-two-dimensional and full two-dimensional models are compared. Two examples of such flow are considered. In the first, plasma is maintained by cw CO2 laser with output power of 2kW and burns in a stream of argon at atmospheric pressure. The results show that quasi-2D model in which the axial flow is given by the relation ρu = ρ0u0(ρ/ρ0)1/2, where ρ and u are density and velocity of the cold gas, fairly well describes the LSP. The second example is the flow through the argon plasma at 1 atm attached to the surface. In this case the simplified formulae do not exist and hence only the results of the two-dimensional model are presented. They are compared with the results of calculations made for constant temperature T = 300 K. It has been found that the presence of the hot region considerably increases the velocity near the surface.